Russian-Kokand relations in the early 19th century (By the example of Philip Nazarov Embassy period) - J.J. Yakobjanov (Proceedings of The ICECRS, 2019)
This article focuses on the Kokand khanate and the political and diplomatic relations of the Russian Empire in the early 19th century. In the course of these diplomatic relations, several embassies were established between the two countries. One of these is Philip Nazarov. This article will tell you about its embassy, its purpose and its consequences.